Regional variation in patients and outcomes in the GLOBAL LEADERS trial. (1st February 2021) - Gao, Chao; Takahashi, Kuniaki; Garg, Scot; Hara, Hironori; Wang, Rutao; Kawashima, Hideyuki; Ono, Masafumi; Montalescot, Gilles; Haude, Michael; Slagboom, Ton; Vranckx, Pascal; Valgimigli, Marco; et al.
Abstract: Background: Despite the overall neutral results of the GLOBAL-LEADERS trial, results from a prespecified subgroup analysis showed that patients from Western Europe had a significantly lower rate of the primary endpoint when treated with ticagrelor monotherapy. Therefore, we aimed to examine the regional disparities in patients' baseline characteristics and their response to ticagrelor monotherapy. Methods: Patients' baseline characteristics and the treatment effects of ticagrelor combined with aspirin for 1 month, followed by ticagrelor monotherapy for 23-months versus 12-months of standard dual antiplatelet therapy (DAPT) were compared according to participating countries. The primary endpoint was a composite endpoint of all-cause death or new Q-wave myocardial infarction at two years. Results: Significant variances in patients' baseline characteristics were found between participating countries. The primary endpoint varied significantly according to the country (Pinteraction  = 0.027). Patients from France (1.6% versus 5.2%, HR: 0.31, 95%CI: 0.13–0.73) and The Netherlands (2.4% versus 4.8%, HR, 0.50, 95%CI: 0.26–0.94) had lower rates of the primary endpoint when allocated to ticagrelor monotherapy, compared with the standard DAPT regimen. Of the 26 baseline and post-randomization factors explored, variance in the rate of complex PCI between countries was identified as the top contributor to this regional interaction. Conclusions: Patients' baseline characteristics varied between participating countries in the GLOBAL-LEADERS trial. There is a significant regional variance in the treatment effect of ticagrelor monotherapy, which could partly be explained by the differences in complex PCI being performed. Clinical Trial Registration: ClinicalTrials.gov (NCT01813435 ). Highlights: A geographic heterogeneity in the primary outcome of the GLOBAL-LEADERS trial was observed. Variances in the complexity of PCI between countries might be the leading cause of the geographic heterogeneity. Stratifying enrollment per country will strengthen the internal validity of the trial results.